2020
DOI: 10.1002/ehf2.12747
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking features of the auto‐epitope essential for β1‐adrenoceptor activation by autoantibodies in chronic heart failure

Abstract: Aims Chronic heart failure (CHF) can be caused by autoantibodies stimulating the heart via binding to first and/or second extracellular loops of cardiac β 1-adrenoceptors. Allosteric receptor activation depends on conformational features of the autoantibody binding site. Elucidating these features will pave the way for the development of specific diagnostics and therapeutics. Our aim was (i) to fine-map the conformational epitope within the second extracellular loop of the human β 1adrenoceptor (β 1 EC II) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…These studies support the hypothesis that β1 adrenoceptor G protein-coupled autoantibodies are a decisive cofactor in chronic HF. 36,37 The present study showed that increased anti-β1 and anti-M2 receptor antibody titers seem to alter nighttime HRV (2:00 to 6:00 a.m.) and exert modulating effects on membrane receptors. A decrease in sympathetic activity was observed during this period in patients with high anti-β1 antibodies, paradoxically to their expected agonist effect.…”
Section: Discussionmentioning
confidence: 48%
“…These studies support the hypothesis that β1 adrenoceptor G protein-coupled autoantibodies are a decisive cofactor in chronic HF. 36,37 The present study showed that increased anti-β1 and anti-M2 receptor antibody titers seem to alter nighttime HRV (2:00 to 6:00 a.m.) and exert modulating effects on membrane receptors. A decrease in sympathetic activity was observed during this period in patients with high anti-β1 antibodies, paradoxically to their expected agonist effect.…”
Section: Discussionmentioning
confidence: 48%
“…141 However, there is increasing appreciation that β1AR autoantibodies may bind to the ECL2 of β1AR regulating receptor function through allosteric modulation without binding to the orthosteric agonist/antagonist site. 10,52,115,122,133 This would allow β1AR autoantibodies to noncanonically modulate agonist and/or antagonist signaling and subsequent cardiac outcomes. The differential signaling outcomes observed with the β1AR autoantibodies from various patients support this scientific premise.…”
Section: Conclusion Challenges and Clinical Implicationsmentioning
confidence: 99%
“…115 These studies are seminal because they have identified the amino acid epitopes recognized by the autoantibody and leveraged this knowledge to provide insights on the potential use of cyclopeptides as therapeutic vehicles to mitigate deleterious effects of b1AR autoantibody. 115 The studies identified the binding sites through the use of monoclonal b1AR autoantibody, but however, patients could harbor a repertoire of autoantibodies recognizing all or a specific composition of these amino acids in the ECL2. In this context, binding of the autoantibody to different extracellular regions of the GPCR could determine differential downstream signaling events resulting in pathogenic versus beneficial outcomes.…”
Section: Autoantibody Subclass-significance Of Igg3mentioning
confidence: 99%
See 2 more Smart Citations